2023
DOI: 10.1101/2023.05.19.541479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The COVID-19 mRNA vaccine Comirnaty induces anaphylactic shock in an anti-PEG hyperimmune large animal model: Role of complement activation in cardiovascular, hematological and inflammatory mediator changes

Abstract: BackgroundComirnaty, Pfizer-BioNTech’s polyethylene-glycol (PEG)-containing Covid-19 vaccine, can cause hypersensitivity reactions (HSRs) in a small fraction of immunized people which can, very rarely, culminate in life-threatening anaphylaxis. A role of anti-PEG antibodies (Abs) has been proposed, but causality has not yet been proven in an animal model. This study aimed to provide such evidence using anti-PEG hyperimmune pigs (i.e., pigs displaying very high levels of anti-PEG Abs). We also sought to find ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Human 77 and animal studies 44, 78, 109 have previously linked these HSRs to C activation by Doxil, while other studies have shown that Doxil and Doxebo are near equivalent in causing C activation 44 . Thus, despite the low level of C activation in vitro and low number of studied sera, the consistent finding of C activation by Comirnaty supports the implication of C activation in Comirnaty-induced HSRs and anaphylaxis 16, 17, 19 . The latter was listed in Comirnaty’s postmarketing survey, updated in Oct 2023, as the 3rd most frequent AE after the cardiac and gastrointestinal complications 110 .…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Human 77 and animal studies 44, 78, 109 have previously linked these HSRs to C activation by Doxil, while other studies have shown that Doxil and Doxebo are near equivalent in causing C activation 44 . Thus, despite the low level of C activation in vitro and low number of studied sera, the consistent finding of C activation by Comirnaty supports the implication of C activation in Comirnaty-induced HSRs and anaphylaxis 16, 17, 19 . The latter was listed in Comirnaty’s postmarketing survey, updated in Oct 2023, as the 3rd most frequent AE after the cardiac and gastrointestinal complications 110 .…”
Section: Discussionsupporting
confidence: 53%
“…Although Comirnaty also contains PEG, its surface density is lower than that in Doxebo (1.5% vs 5%), which may explain the small but consistent C4d rise in 3 of 5 sera in Figure 2C. In other experimental systems, e.g., anti-PEG hyperimmune pigs 19, 83 , or even humans with extremely high anti-PEG antibody levels in their blood 18 , the involvement of classical pathway in C activation by PEGylated nanoparticles may become more prominent.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations